The role of differentially expressed salivary microRNA in oral squamous cell carcinoma. A systematic review - Al Rawi, Natheer; Elmabrouk, Neibal; Abu Kou, Rawan; Mkadmi, Sara; Rizvi, Zuha; Hamdoon, Zaid (Archives of oral biology, 2021)
•Saliva is a suitable medium for extraction of micro-RNA for diagnosis of oral cancer.•25 micro-RNA were differentially expressed in saliva of oral cancer patients.•Identified micro-RNA could be used in personalized therapy for oral cancer patients. This study aims to systematically review the role of differentially expressed microRNA (miRNA) in saliva as potential biomarkers in oral cancer patients. PubMed, Scopus and EBSCO online data bases were used as well as manual searching to extract studies from January 2008 up to October 2020. A total of 14 studies that met the eligibility criteria were included. All selected studies were of case-control type. A total of 25 differentially expressed miRNAs were identified. Thirteen of these miRNAs (Let-7a, miR 27, miR 34, miR 92, miR 124, miR 125a, miR 136, miR139 miR 145, miR 146a, miR 200a, miR 205 and miR 375) were downregulated and other twelve (miR 9, miR 21, miR 31, miR 122, miR 134, miR 184, miR 191, miR 196a, miR 196b, miR 412, miR 512 and miR 8392) were upregulated. Four miRNAs were evaluated in more than one study (miR21, miR31, miR125 and miR 200). According to these results, salivary miRNA can aid in diagnosis and prognosis of oral squamous cell carcinoma (OSCC). However, controlled clinical trials with a large sample size are required to validate the differentially expressed miRNAs of the present review.